Pengaruh Literasi Keuangan dan Artificial Intelligence Terhadap Minat Investasi Pasar Modal Pada Mahasiswa Prodi Akuntansi di Kota Medan - Ardhansyah Putra Hrp; Julianto Hutasuhut; Indra Fauzi (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2026)
The purpose of this study was to analyze the effect of Financial Literacy, and Artificial Intelligence on Capital Market Investment Interest among Accounting Study Program Students at Medan City. The study population consisted of 213 active students from the Accounting Study Program at the Faculty of Economics and Business at Medan City. The research sample was selected using a purposive sampling technique, resulting in a sample of 172 students who met specific criteria. Data collection used a questionnaire method. The method used in this study was multiple regression analysis with the help of SPSS software version 22. The results of the study showed that the independent variables had a significant effect on the dependent variable. Based on the results of the determination coefficient test, the R-squared value was 41%, with the remaining 59% attributed to other variables not included in this study and based on the results of the partial test of the financial literacy variable, budgeting strategy, and artificial intelligence, affected investment interest in the capital market.